cal2 - choi (kc24547) HW02 BERG (56525) 1 This print-out...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: choi (kc24547) HW02 BERG (56525) 1 This print-out should have 10 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. 001 10.0 points Find all functions g such that g ( x ) = 3 x 2 + x + 2 x . 1. g ( x ) = x parenleftbigg 3 5 x 2 + 1 3 x + 2 parenrightbigg + C 2. g ( x ) = 2 x parenleftbigg 3 5 x 2 + 1 3 x + 2 parenrightbigg + C cor- rect 3. g ( x ) = 2 x ( 3 x 2 + x 2 ) + C 4. g ( x ) = 2 x parenleftbigg 3 5 x 2 + 1 3 x 2 parenrightbigg + C 5. g ( x ) = 2 x ( 3 x 2 + x + 2 ) + C 6. g ( x ) = x ( 3 x 2 + x + 2 ) + C Explanation: After division g ( x ) = 3 x 3 / 2 + x 1 / 2 + 2 x 1 / 2 , so we can now find an antiderivative of each term separately. But d dx parenleftbigg ax r r parenrightbigg = ax r 1 for all a and all r negationslash = 0. Thus 6 5 x 5 / 2 + 2 3 x 3 / 2 + 4 x 1 / 2 = 2 x parenleftbigg 3 5 x 2 + 1 3 x + 2 parenrightbigg is an antiderivative of g . Consequently, g ( x ) = 2 x parenleftbigg 3 5 x 2 + 1 3 x + 2 parenrightbigg + C with C an arbitrary constant. 002 10.0 points Determine f ( t ) when f ( t ) = 6( t + 1) and f (1) = 2 , f (1) = 4 . 1. f ( t ) = t 3 3 t 2 + 7 t 1 2. f ( t ) = t 3 + 3 t 2 7 t + 7 correct 3. f ( t ) = 3 t 3 6 t 2 + 7 t + 0 4. f ( t ) = 3 t 3 + 3 t 2 7 t + 5 5. f ( t ) = t 3 6 t 2 + 7 t + 2 6. f ( t ) = 3 t 3 + 6 t 2 7 t + 2 Explanation: The most general anti-derivative of f has the form f ( t ) = 3 t 2 + 6 t + C where C is an arbitrary constant. But if f (1) = 2, then f (1) = 3 + 6 + C = 2 , i.e., C = 7 . From this it follows that f ( t ) = 3 t 2 + 6 t 7 . The most general anti-derivative of f is thus f ( t ) = t 3 + 3 t 2 7 t + D , where D is an arbitrary constant. But if f (1) = 4, then f (1) = 1 + 3 7 + D = 4 , i.e., D = 7 . Consequently, f ( t ) = t 3 + 3 t 2 7 t + 7 . choi (kc24547) HW02 BERG (56525)...
View Full Document

Page1 / 6

cal2 - choi (kc24547) HW02 BERG (56525) 1 This print-out...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online